Impurities Effect on Carbonate Reactive Crystallization for the Wastewater. (21st January 2013) - Shimizu, Y.; Hirasawa, I.
Abstract : Reactive crystallization designed to separate nickel or copper ion from effluents has been advanced for applying to actual industrial wastewater containing impurities. In the primary reaction of this method, metal sulfate solution reacts with sodium carbonate solution in a semibatch crystallizer. In the present study, during the process of nickel or copper ions incorporation, inhibitory effect on seed growth of impurities, like cobalt, manganese, zinc, and borate and phosphate ions, was investigated. Through the 8-hour reactive crystallization, obtained particles' characters and metals removal efficient were examined. Considering analyses data on metal component ratio in produced crystals, metal ions initial uptake rate was found to be different by the kind of seeds and impurities. And the centrifugation was performed against obtained crystals aimed for examining target metal purity improvement. The results indicated that copper components can incorporate and remove other metal ions easily. In addition, when the anions are used as impurities, depending on the kind of anions, the effect of damaging the surface of seeds or producing many fine particles has been confirmed.